The effect of digital economy on rural workforce occupation transformation ability: Evidence from China - Bin Xiong; Qi Sui (Humanities & Social Sciences Communications)
Abstract Occupation transformation is a frequently discussed topic among scientists, politicians and the general public. Along with the development of science and technology, how to take advantage of the digital economy to improve the transformation ability of rural labor has become the key to rural revitalization. Using the China Labor Dynamics Survey data (CLDS), this research empirically investigates the influence of digital economy involvement on rural labor force occupation transformation ability, drawing on the sustainable livelihoods framework. The findings indicate that engagement in the digital economy can greatly improve the labor force’s occupation transformation ability. Rural workers promote their occupation self-efficacy and subjective well-being by participating in the digital economy, which improves the ability for occupational transformation. Further research revealed that the digital economy has a “spillover effect” on the labor force’s occupation transformation ability. Meanwhile, machine learning analysis revealed that age, house value, and total household income capacity are the primary elements driving heterogeneity in the digital economy’s ability to impact the occupation transformation ability. Overall, this research sheds new light on the long-term development of rural labour force employment in the digital economy era.